THE EFFECT OF INVESTMENT KNOWLEDGE, MINIMUM INVESTMENT CAPITAL, AND MOTIVATION ON INVESTMENT INTEREST - Romadon, Ahmad Sahri (Jurnal Ekonomi dan Bisnis Airlangga, 2023)
Introduction: This study aims to empirically examine the effect of Investment knowledge, minimum investment capital, and motivation on Investment Interest (Study on students of the Faculty of Economics, University of Semarang). Methods: This research is a quantitative study processed using SPSS version 23 and the sample in this study were 125 respondents. The dependent variable used in this study is investment interest, and the independent variables used are investment knowledge, minimum investment capital, and motivation. Results: The results of this study indicate that investment knowledge, minimum investment capital, and motivation have a positive and significant effect on investment interest. Conclusion and suggestion: The researcher provides advice to prospective investors to increase their knowledge of the basics of investment which can be taken into consideration when starting an investment. Capital is also a consideration for investing, with a minimum investment capital policy, one can invest with the minimum possible capital. Increasing motivation from yourself and others is also important to foster investment interest.